Analysis of morphological features and chemical properties of the dried seabed soils of the North – Eastern Aral Sea region (Journal of Geography and Environmental Management, 2021)
On the dried-out surface of the Aral Sea, peculiar soil-formation processes take place. First, littoral soils whose development proceeds according to the zonal desert type. The general pattern is weak development of soil-forming processes on the background of strong initial salinity and carbonation.As a result of conducted field researches the basic types of soils and their morphological, chemical properties, content of heavy metals (gross and mobile) and specific features of salinization of soils of north-eastern Aral region are determined.The following soil types have been identified: typical solonchak, takyr-like and takyr solonchak, meadow solonchak, seaside solonchak, desert sand, brown desert non-saline soils. A comparative assessment of soil changes in the Eastern Aral Sea region as a result of the Aral Sea desiccation has been carried out. The leading factor of soil cover formation and development on the exposed seabed surfaces is the desert climate, which determines the development of salinization process after the sea receded, followed by rapid aridization of the area.
Keywords: soil, solonchak, salinity, soil morphology, carbonates, absorbed bases, heavy metals, deflation, aridization.